The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3354/meps09384
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient exposure causes epiphytic changes and coincident declines in two temperate Australian seagrasses

Abstract: We undertook a long-term (27 mo) field experiment to test if a chronic increase in water column nutrients could cause a decline in 2 temperate Australian seagrasses and if this decline could be linked to nutrient-mediated changes in epiphytes. Two seagrasses, Amphibolis antarctica and Posidonia sinuosa, were exposed to minor increases (~2 to 5×) in nutrient (N, P) concentrations utilising slow-release fertiliser over a 15 mo period at a shallow (~2 m depth), oligotrophic marine site in Gulf St Vincent, South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…High nutrient availability affects seagrasses in several ways. The major effects are indirectly caused by the proliferation of phytoplankton, epiphytic microalgae and fast-growing drifting macroalgae promoting light attenuation (Sand-Jensen & Borum 1991, Hernández et al 1997, Valiela et al 1997, Hauxwell et al 2001, McGlathery 2001, Bryars et al 2011, Lyons et al 2012 or increasing the sedi-ment organic matter load, which may reduce oxygen levels and increase the risk of anoxia (Greve et al 2003) and sulfide intrusion into the plants (Holmer & Bondgaard 2001, Borum et al 2005, Pérez et al 2007, Olivé et al 2009). Furthermore, there may be a direct effect of high nutrient availability on seagrasses since exposure to high concentrations of NH 4 + can be toxic to higher plants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…High nutrient availability affects seagrasses in several ways. The major effects are indirectly caused by the proliferation of phytoplankton, epiphytic microalgae and fast-growing drifting macroalgae promoting light attenuation (Sand-Jensen & Borum 1991, Hernández et al 1997, Valiela et al 1997, Hauxwell et al 2001, McGlathery 2001, Bryars et al 2011, Lyons et al 2012 or increasing the sedi-ment organic matter load, which may reduce oxygen levels and increase the risk of anoxia (Greve et al 2003) and sulfide intrusion into the plants (Holmer & Bondgaard 2001, Borum et al 2005, Pérez et al 2007, Olivé et al 2009). Furthermore, there may be a direct effect of high nutrient availability on seagrasses since exposure to high concentrations of NH 4 + can be toxic to higher plants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Low irradiance can negatively affect seagrasses by reducing their photosynthesis with less energy for growth and also restricting their depth distribution to shallower waters (Bryars et al, 2011). For example, Abal et al (1994) showed that if Zostera capricorni receives, less than 100-500 μmol photons m −2 s −1 , at the midday peak, its respiration demand exceeds the rate of carbon fixation resulting in reduced growth rates.…”
Section: Introductionmentioning
confidence: 99%
“…Posidonia rhizomes form a complex matrix where many individual plants overlap, rather than 367 being a single clonal individual (Bryars, et al, 2011), making the removal of small amounts 368 of above ground biomass unlikely to destroy entire plants. While sub-sampling itself does not 369 appear to send seagrass meadows into significant decline (Bryars, et impacts for two reasons.…”
mentioning
confidence: 99%